Logistic Service Quality (LSQ) on Shopee Xpress / Aida Sabilla ... [et al.] - Aida Sabilla; Sekar Arum, Cahyaning; Alfaridi, Nursery; Simarmata, Juliater (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
The COVID-19 pandemic, which began in mid-2020, has driven a significant shift towards online buying and selling through E-commerce platforms. Notably, Shopee has experienced a surge in website visits as a result. To cater to this demand, Shopee relies on Last Mile Delivery, facilitated by their service called Shopee Xpress. In order to maintain a competitive edge in the crowded shipping services market, a thorough analysis and evaluation of customer perceptions regarding Shopee Xpress' expedition services have been conducted. The research employs two key methodologies: Logistics Service Quality (LSQ) and Important Performance Analysis (IPA). Data was collected through a questionnaire structured around five variables and fifteen LSQ indicators. Among these variables, the Image variable emerged as the one that best aligned with customer expectations and actual performance. The IPA approach further yielded a prioritized mapping of areas that require evaluation and enhancement. This mapping is based on indicators' relative importance. From this prioritization, a series of proposed enhancements have been formulated for Shopee Xpress. In conclusion, the COVID-19 pandemic catalyzed a surge in online transactions, prompting E-commerce platforms like Shopee to adapt. Shopee Xpress, the platform's Last Mile Delivery service, became pivotal in meeting this demand. The research's amalgamation of LSQ and IPA methodologies provided valuable insights into customer perceptions. The resulting identification of the Image variable as the most significant alignment between expectations and performance underscores its importance. The IPA-driven prioritization of indicators also paved the way for targeted improvements, shaping a roadmap for Shopee Xpress' ongoing enhancement.